Recent Advances in Development of Functional Spider Silk-Based Hybrid Materials - Kiseleva, Aleksandra P.; Krivoshapkin, Pavel V.; Krivoshapkina, Elena F. (Frontiers in Chemistry, 2020)
Silkworm silk is mainly known as a luxurious textile. Spider silk is an alternative to silkworm silk fibers and has much more outstanding properties. Silk diversity ensures variation in its application in nature and industry. This review aims to provide a critical summary of up-to-date fabrication methods of spider silk-based organic-inorganic hybrid materials. This paper focuses on the relationship between the molecular structure of spider silk and its mechanical properties. Such knowledge is essential for understanding the innate properties of spider silk as it provides insight into the sophisticated assembly processes of silk proteins into the distinct polymers as a basis for novel products. In this context, we describe the development of spider silk-based hybrids using both natural and bioengineered spider silk proteins blended with inorganic nanoparticles. The following topics are also covered: the diversity of spider silk, its composition and architecture, the differences between silkworm silk and spider silk, and the biosynthesis of natural silk. Referencing biochemical data and processes, this paper outlines the existing challenges and future outcomes.